Simplified discriminant parameters for sarcopenia among patients undergoing haemodialysis. Issue 6 (4th September 2022) - Kakita, Daisuke; Matsuzawa, Ryota; Yamamoto, Shohei; Suzuki, Yuta; Harada, Manae; Imamura, Keigo; Yoshikoshi, Shun; Imai, Hiroto; Osada, Shiwori; Shimokado, Kiyoshi; Matsunaga, Atsuhiko; Tamaki, Akira
Abstract: Background: Patients with end‐stage renal disease (ESRD) are at an increased risk of developing sarcopenia, which can lead to various adverse health outcomes. Although the diagnosis of sarcopenia is essential for clinical management, it is not feasible in routine clinical practice for populations undergoing haemodialysis because it is time‐consuming and resources are limited. Serum creatinine levels in patients with ESRD have been gaining attention as a screening parameter for sarcopenia because serum creatinine is a routinely measured byproduct of skeletal muscle metabolism. This study aimed to evaluate the discriminative ability of the creatinine‐derived index for sarcopenia in patients undergoing haemodialysis. Methods: We diagnosed sarcopenia according to the Asian Working Group for Sarcopenia (AWGS) 2 criteria in 356 clinically stable outpatients with ESRD enrolled from three dialysis facilities. We adopted the modified creatinine index as a simplified discriminant parameter for sarcopenia in addition to the calf circumference, SARC‐F score, and combination of both (i.e. SARC‐CalF score), which are recommended by the AWGS. Receiver operating characteristic analysis and logistic regression analysis were conducted to evaluate the discriminative ability of the modified creatinine index for sarcopenia. Results: Of the study participants, 142 (39.9%) were diagnosed with sarcopenia. The areas under the curve of the modified creatinine index against sarcopenia in the male and female participants were 0.77 (95% confidence interval [CI]: 0.71 to 0.83) and 0.77 (95% CI: 0.69 to 0.85), respectively. All simplified discriminant parameters were significantly associated with sarcopenia, even after adjusting for patient characteristics and centre. In the comparison of the odds ratios for sarcopenia for 1‐standard deviation change in the simplified discriminant parameters, the odds ratio of the modified creatinine index was 1.92 (95% CI: 1.15 to 3.19), which was lower than that of the calf circumference (odds ratio: 6.58, 95% CI: 3.32 to 13.0) and similar to that of the SARC‐F (odds ratio: 1.57, 95% CI: 1.14 to 2.16) and SARC‐CalF scores (odds ratio: 2.36, 95% CI: 1.60 to 3.47). Conclusions: This study revealed a strong association between the creatinine‐derived index and sarcopenia in patients undergoing haemodialysis. The modified creatinine index was equal or superior to those of SARC‐F and SARC‐CalF score in discriminability for sarcopenia. However, the ability of the calf circumference to discriminate sarcopenia is extremely high, and further study is needed to determine whether it can be used to detect deterioration of muscle mass and function over time.